The anxious aspects of insecure attachment styles are associated with depression either in pregnancy or in the postpartum period - Bianciardi, Emanuela (Ann Gen Psychiatry, 2020)
BACKGROUND: Perinatal depression (PND) is a major complication of pregnancy and many risk factors have been associated with its development both during pregnancy and postpartum. The transition to motherhood activates the attachment system. The aim of our study was to investigate the relationship between women’s attachment style (AS) and PND in pregnancy, and 1 month after childbirth, in a large cohort of women. We hypothesized that different patterns of AS were associated with either antenatal or postnatal depression. We, further, explored the role of other possible risk factors such as life-stress events. METHODS: A final sample of 572 women was enrolled. At the third trimester of pregnancy, clinical data sheet and self-report questionnaires (ASQ, PSS, LTE-Q, and EPDS) were administered. One month after delivery, EPDS was administered by telephone interview. RESULTS: We found 10.1% of the women with depression during pregnancy and 11.1% in the postpartum period. The first logistic regression showed that ASQ-CONF subscale (OR = 0.876, p < 0.0001), ASQ-NFA subscale (OR = 1.097, p = 0.002), foreign nationality (OR = 2.29, p = 0.040), low education levels (OR = 0.185, p = 0.012), PSS total score (OR = 1.376, p = 0.010), and recent life adversities (OR = 3.250, p = 0.012) were related to EPDS ≥ 14 during pregnancy. The second logistic regression showed that ASQ-PRE subscale (OR = 1.077, p < 0.001) and foreign nationality (OR = 2.88, p = 0.010) were related to EPDS ≥ 12 in the postpartum period. CONCLUSIONS: Different dimensions of anxious insecure AS were, respectively, associated with either antenatal or postnatal depression. These findings support the literature investigating subtypes of perinatal depression. The PND may be heterogeneous in nature, and the comprehension of psychopathological trajectories may improve screening, prevention, and treatment of a disorder which has a long-lasting disabling impact on the mental health of mother and child. We provided a rationale for targeting an attachment-based intervention in this group of women.